Distinct Embryonic Origin and Injury Response of Resident Stem Cells in Craniofacial Muscles - Cheng, Xu; Shi, Bing; Li, Jingtao (Frontiers in Physiology, 2021)
Craniofacial muscles emerge as a developmental novelty during the evolution from invertebrates to vertebrates, facilitating diversified modes of predation, feeding and communication. In contrast to the well-studied limb muscles, knowledge about the craniofacial muscle stem cell biology only starts to be gathered up recently. Craniofacial muscles are distinct from their counterparts in other regions in both embryonic origin and injury response. Compared with the somite-derived limb muscles, the pharyngeal arch-derived craniofacial muscles demonstrate delayed myofiber reconstitution and prolonged fibrosis during repair. The regeneration of muscle is orchestrated by a blended source of stem/progenitor cells, including myogenic muscle satellite cells (MuSCs), mesenchymal fibro-adipogenic progenitors (FAPs) and other interstitial progenitors. Limb muscles host MuSCs of Pax3 lineage and FAPs derive from the mesoderm, while craniofacial muscles provide niche for MuSCs of Msep1 lineage and FAPs from the ectoderm-derived neural crest. Both in vivo and in vitro data revealed distinct patterns of proliferation and differentiation in these craniofacial muscle stem/progenitor cells. Additionally, the proportion of cells from different embryonic origin changes throughout the postnatal development in craniofacial muscles, creating a more dynamic niche environment than other muscles. In-depth comparative studies in the stem cell biology between craniofacial and limb muscles might inspire novel therapeutics to improve the management of myopathic disease. With most up-to-date literature, we intent to delineate pivotal cell populations regulating craniofacial muscle repair and identify clues that might bridge the gap between the distinct embryonic origin and injury response in craniofacial muscles.